-34=5x+3(x+2)

Simple and best practice solution for -34=5x+3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=5x+3(x+2) equation:


Simplifying
-34 = 5x + 3(x + 2)

Reorder the terms:
-34 = 5x + 3(2 + x)
-34 = 5x + (2 * 3 + x * 3)
-34 = 5x + (6 + 3x)

Reorder the terms:
-34 = 6 + 5x + 3x

Combine like terms: 5x + 3x = 8x
-34 = 6 + 8x

Solving
-34 = 6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-34 + -8x = 6 + 8x + -8x

Combine like terms: 8x + -8x = 0
-34 + -8x = 6 + 0
-34 + -8x = 6

Add '34' to each side of the equation.
-34 + 34 + -8x = 6 + 34

Combine like terms: -34 + 34 = 0
0 + -8x = 6 + 34
-8x = 6 + 34

Combine like terms: 6 + 34 = 40
-8x = 40

Divide each side by '-8'.
x = -5

Simplifying
x = -5

See similar equations:

| f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) | | 3(w+7)=-3 | | 8(1-4x)+8(x+3)=32 | | 8(1-4x)+8(m+3)=32 | | 4(0+1)=4(x+8) | | 22+2z=52 | | 9d+1=8d-18 | | 3(g+8)-2=7 | | 6x^6-96x^2=0 | | 4x+8=15x-3x | | -4=5+3n | | 0=2(sin)x*2(cos)x |

Equations solver categories